PENGEMBANGAN KUALITAS STUDI ILMU ADMINISTRASI PUBLIK DI INDONESIA (POKOK-POKOK PIKIRAN MENUJU PARADIGMA BARU ILMU ADMINISTRASI PUBLIK): Administrative Science, paradigms, competencies - admin, admin (JAMAK, 2014)
This paper wants to build a construction of a new paradigm in the study of th e science of public administration.Discussion of a new paradigm of public administration science essentially evaluative and projections.Evaluation is needed to assess the system, curriculum, teaching methods, and competencies are applied over the years.Whi le projections directed towards the achievement of the implementation of the system and pattern learning/learning outcomes in the university with the development of the situation, whether that is happening in the present or in anticipation of future conditions.Specifically, there are three topics that are relevant and logical according to the author to put forward in this paper.Highlights are: first, the characteristics of the science of public administration, and second, the development of the public admi nistration discipline in Indonesia, and the third, a new paradigm of public administration science studies.